Smoking and dementia in male British doctors: prospective study. - Doll, R; Peto, R; Boreham, J; Sutherland, I (2000)
OBJECTIVE: To assess the possible association between smoking and dementia. DESIGN: Prospective study. SETTING: Cohort of British male doctors followed up since 1951. SUBJECTS: 34 439 male British doctors, with 24 133 deaths recorded. RESULTS: For all types of dementia combined the relative risk was 0.96 (95% confidence interval 0.78 to 1.18), based on 473 deaths at a mean age of 81 years. For probable or definite Alzheimer's disease, the relative risk in continuing smokers was 0.99 (0.78 to 1.25), based on 370 deaths at a mean age of 82 years. In aggregate, however, the other prospective studies indicate a direct, although not clearly significant, association between smoking and the onset of dementia in general and of Alzheimer's disease in particular. CONCLUSIONS: Contrary to previous suggestions persistent smoking does not substantially reduce the age specific onset rate of Alzheimer's disease or of dementia in general. If anything, it might increase rather than decrease the rate, but any net effect on severe dementia cannot be large in either direction.